2021
DOI: 10.1002/anie.202001654
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Diels–Alder Reaction Mechanism since the 1930s: Woodward, Houk with Woodward, and the Influence of Computational Chemistry on Understanding Cycloadditions

Abstract: This review article describes the evolution of Woodward's mechanistic thinking, beginning in the late 1930s and early 1940s with his proposal of a charge‐transfer mechanism for the Diels–Alder reaction, eventually leading to the Woodward–Katz two‐stage concerted mechanism in 1959, and then to its mechanistic solution in terms of orbital symmetry control. Houk′s research in the Woodward labs, testing the predictions of this theory, is described. Subsequent modern calculations with quantum mechanics and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 98 publications
5
99
0
1
Order By: Relevance
“…In contrast to on‐surface Ullmann or Glaser type coupling reactions the number of atoms in precursor 1 and product 3 is identical, which relates to the atom economy of the DA reaction [3] . However, the number of hydrogen atoms is not conserved in the complete reaction pathway.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to on‐surface Ullmann or Glaser type coupling reactions the number of atoms in precursor 1 and product 3 is identical, which relates to the atom economy of the DA reaction [3] . However, the number of hydrogen atoms is not conserved in the complete reaction pathway.…”
Section: Figurementioning
confidence: 99%
“…First reported in 1928 by Otto Diels and Kurt Alder while studying the products from the reaction of cyclopentadiene with quinone, [1] in few years the Diels–Alder reaction became one of the most popular reactions in organic synthesis [2] . According to Roald Hoffman, the distinguished pioneer in the study of organic reactivity, the relevant role of the DA reaction is due to “…the economy it brings to synthesis, and the frequency of the six‐membered ring in organic chemistry” [3] …”
Section: Figurementioning
confidence: 99%
“…Diels-Alder (DÀ A) cycloaddition reaction was firstly proposed by Otto Diels and Kurt Alder who obtained the 1950 Nobel Prize for their discovery. [1] It is known that this reaction proceeds usually in a concerted way involving the formation of two new CÀ C bonds through a six-membered cyclic transition state. [2] Therefore, this reaction gives a simple and general entry for the synthesis of a multitude of six-membered cyclic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The Diels-Alder reaction is one of the most important cycloaddition reactions in organic chemistry and was honoured with the Nobel Prize in chemistry in 1950. Since then, many new discoveries in its research field were reported, [1] for instance the hetero Diels-Alder reaction as a direct variation of its original but with hetero-atoms like N, O and/or S in the diene or dienophile functionality. [2] Especially nitroso compounds are interesting substrates for this reaction since the obtained 1,2-oxazine unit is represented in biological active molecules [3] or can be used as strategic intermediate in their total synthesis, for example, in dihydronarciclasine.…”
mentioning
confidence: 99%